Effects of a P2X7 receptor antagonist on myenteric neurons in the distal colon of an experimental rat model of ulcerative colitis. - Evangelinellis, Mariá Munhoz; Souza, Roberta Figueiroa; Mendes, Cristina Eusébio; Castelucci, Patricia (Histochemistry & Cell Biology, 2022)
Inflammatory bowel diseases (IBDs) are chronic diseases of the gastrointestinal tract that include ulcerative colitis and Crohn's disease and affect enteric neurons. Research has shown that Brilliant Blue G (BBG), a P2X7 receptor antagonist, restores enteric neurons following ischemia and reperfusion. This study aimed to evaluate the effect of BBG on myenteric neurons of the distal colon in an experimental rat model of ulcerative colitis. Colitis was induced by injection of 2,4,6-trinitrobenzene sulfonic acid (TNBS) into the large intestine. BBG was administered 1 h after colitis induction and for five consecutive days thereafter. Distal colons were collected 24 h or 7 days after TNBS injection. The animals were divided into 24-h and 7-day sham (vehicle injection rather than colitis induction), 24-h colitis, 24-h BBG, 7-day colitis and 7-day BBG groups. The disease activity index (DAI), neuronal density and profile of neuronal nitric oxide synthase (nNOS)-, choline acetyltransferase (ChAT)- and P2X7 receptor-immunoreactive enteric neurons were analyzed, and histological analysis was performed. The results showed recovery of the DAI and histological tissue integrity in the BBG groups compared to those in the colitis groups. In addition, the numbers of neurons positive for nNOS, ChAT and the P2X7 receptor per area were decreased in the colitis groups, and these measures were recovered in the BBG groups. Neuronal size was increased in the colitis groups and restored in the BBG groups. In conclusion, BBG is effective in improving experimental ulcerative colitis, and the P2X7 receptor may be a therapeutic target.